Implications of accreditation criteria when transforming a traditional nursing curriculum to a competency-based curriculum - Yvonne Botma (Elsevier, 2014)
Nurse educators in a resource-poor country have identified the need to change from content-driven curriculum to a competency-based curriculum. A rapid assessment was done to determine the standing of nursing education in the country. Structured interviews were conducted with educational and administrative staff as well as students at all six nursing schools in Lesotho. Programme design, human resources, teaching and learning, physical resources, and programme accreditation were addressed during the rapid assessment. The results were uniform due to the country being small and four nursing schools forming a consortium. A traditional content-driven three-year diploma programme that renders a single-qualified nurse is being offered. A five-year degree programme in nursing is being offered by the only university in the country. Nursing schools are resource-poor with limited or no external funding sources. Changing to and sustaining a competency-based curriculum will require extensive empowerment of nurse educators. Professional governing bodies should produce supporting rules and regulations.